Mitohormesis : la clé de voûte de la résistance thérapeutique des cellules cancéreuses - Boët, Emeline; Saland, Estelle; Skuli, Sarah; Griessinger, Emmanuel; Sarry, Jean-Emmanuel (Comptes Rendus Biologies)
A large body of literature highlights the importance of energy metabolism in the response of haematological malignancies to therapy. In this review, we are particularly interested in acute myeloid leukaemia, where mitochondrial metabolism plays a key role in response and resistance to treatment. We describe the new concept of mitohormesis in the response to therapy-induced stress and in the initiation of relapse in this disease.